2013
DOI: 10.1242/dev.091868
|View full text |Cite
|
Sign up to set email alerts
|

QUIRKY interacts with STRUBBELIG and PAL OF QUIRKY to regulate cell growth anisotropy during Arabidopsis gynoecium development

Abstract: Organ morphogenesis largely relies on cell division and elongation, which need to be both coordinated between cells and orchestrated with cytoskeleton dynamics. However, components that bridge the biological signals and the effectors that define cell shape remain poorly described. We have addressed this issue through the functional characterisation of QUIRKY (QKY), previously isolated as being involved in the STRUBBELIG (SUB) genetic pathway that controls cell-cell communication and organ morphogenesis in Arab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 81 publications
5
55
1
Order By: Relevance
“…Although the presence of SUB is not constrained to PD, localization of QKY appears to be restricted to PD. With respect to the subcellular localization of QKY, our results differ from a recent study, that reported QKY to be present at the PM (Trehin et al, 2013). Trehin et al, however, used a nonfunctional reporter carrying EGFP at the C terminus of QKY.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Although the presence of SUB is not constrained to PD, localization of QKY appears to be restricted to PD. With respect to the subcellular localization of QKY, our results differ from a recent study, that reported QKY to be present at the PM (Trehin et al, 2013). Trehin et al, however, used a nonfunctional reporter carrying EGFP at the C terminus of QKY.…”
Section: Discussioncontrasting
confidence: 99%
“…On selective medium, yeast growth was observed when QKYΔPRT_C was combined with the ICD of SUB (Fig. 7D), demonstrating that QKY can interact with the ICD of SUB in this assay, extending previous results (Trehin et al, 2013).…”
Section: Sub:egfp and Mcherry:qky Interact Physically In Plantasupporting
confidence: 87%
See 2 more Smart Citations
“…including mctp1-1 (ftip1-1) (Liu et al, 2012), mctp15 (qky-14) (Trehin et al, 2013), and mctp6-1 370 show the late-flowering phenotype (Fig. 10, A-D (Liu et al, 2012) (Fig.…”
mentioning
confidence: 99%